2019
DOI: 10.1111/ecno.12142
|View full text |Cite
|
Sign up to set email alerts
|

Migration, remittances and human capital investment in Kenya

Abstract: This paper investigates the relationship between international migration, remittances, and human capital investment in Kenya. We use household‐level data from the 2009 Kenya Migration Household Survey (which was part of the Africa Migration Project) to test our hypothesis and uncover a positive and significant relationship between the amount of international remittances a household receives and the amount of expenditures allocated to education (for all levels of education). We consider various robustness check… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 25 publications
4
10
0
Order By: Relevance
“…The remittances received by the household increases by one unit, which will lead to an increase in the human capital index or human capital by 0.485 units. This study supports the finding of Acharya and Gonzalez (2014) and Hines and Simpson (2019). It has been observed that if the income per capita of the household increases by one percent, it will lead to an increase in the human capital index or human capital of the household by 0.885 units [Mincer (1981), Benhabib and Speigel (1994)].…”
Section: Empirical Findingssupporting
confidence: 88%
“…The remittances received by the household increases by one unit, which will lead to an increase in the human capital index or human capital by 0.485 units. This study supports the finding of Acharya and Gonzalez (2014) and Hines and Simpson (2019). It has been observed that if the income per capita of the household increases by one percent, it will lead to an increase in the human capital index or human capital of the household by 0.885 units [Mincer (1981), Benhabib and Speigel (1994)].…”
Section: Empirical Findingssupporting
confidence: 88%
“…For example, Arguillas and Williams (2010) report that migrant parents who send remittances back home more frequently, high volume of remittances and work overseas for long periods, their older children (19-21 years old) have a higher tendency to continue until college level. In line with that argument, Hines and Simpson (2019) find that migrant households which receive remittances are more likely to allocate funds and spend more on education-related expenses. Similarly, Amuedo-Dorantes and Pozo (2010) conclude that remittances from migrant parents increase their children's attendance in school.…”
Section: Undocumented Migrant Childrensupporting
confidence: 60%
“…This compares with studies that emigration induces more human capital formation in home countries (Mountford, 1997;Stark et al, 1997Stark et al, , 1998Stark and Wang, 2002;Edwards and Ureta, 2003;Piracha et al, 2013;Hines and Simpson, 2018). Migrant's household members may use remittances to boost educational attainment as migrant families can afford to pay school fees, transportation, and school essentials, or hire labor to work in households, businesses, and farms.…”
Section: Introductionmentioning
confidence: 44%